Implementation of just in time for cost saving of 4-wheel tractor manufacturing preparation process (case study on pt iseki indonesia) - Huda, Ahmad Saiful; Suriyok, Khamdan; Arumsari, Yuni Kusuma; Syarifudin, Arif; Yanuar Putra, Rama Dwi (Institute of Computer Science (IOCS), 2025)
Business development is growing and creating competition for business actors by producing competitive, innovative and high-tech products. Research Object of PT Iseki Indonesia Pasuruan. Based on observations with management that the implementation of the Just In Time System is still high production costs so that the cost of the product is too high resulting in the product not being able to compete in the market. This type of research uses a qualitative descriptive approach. The data processed are primary data in the form of production records and the results of interviews with management. Based on the results of the study, it was shown that the application of the Just In Time system was proven to reduce the cost of part preparation, as evidenced by changing the preparation for the MFGC type tractor part taking which previously took 1405 hours or Rp. 78,680,000, after the implementation of the Just In Time system, it changed to 261 hours. or Rp. 14,616,000. So the total cost savings after implementing the Just In Time system is Rp. 64,064,000. The application of the Just In Time system has indeed been proven to be able to eliminate many useless things in the company